2018
DOI: 10.1128/iai.00239-18
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax Merozoite Surface Protein 1 Paralog as a Mediator of Parasite Adherence to Reticulocytes

Abstract: parasites preferentially invade reticulocytes in human beings. merozoite surface protein 1 (PvMSP1) and PvMSP1 paralog (PvMSP1P) may have important functions in reticulocyte adherence during invasion. These proteins share similar structures, including the presence of two epidermal growth factor (EGF)-like and glycosylphosphatidylinositol (GPI)-anchored domains at the C terminus. However, there have been no reports concerning the functional activity of PvMSP1P in reticulocyte adherence during invasion. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 51 publications
3
18
0
Order By: Relevance
“…Interestingly, all the 12 cysteine residues within the double EGF domains were conserved within the 43 isolates (including the lab adapted strains) indicating conserved functional activity. This conservation of the 12 cysteine residues was also observed for the C-terminal 19 kDa fragment of PvMSP1P and PkMSP1P [26] and binding activity to reticulocytes in P. vivax have been reported [14,2729]. Sliding window plot analysis of Tajima’s D across the full-length pkmsp8 gene also indicated most values below 0 indicating purifying selection (Fig.…”
supporting
confidence: 65%
“…Interestingly, all the 12 cysteine residues within the double EGF domains were conserved within the 43 isolates (including the lab adapted strains) indicating conserved functional activity. This conservation of the 12 cysteine residues was also observed for the C-terminal 19 kDa fragment of PvMSP1P and PkMSP1P [26] and binding activity to reticulocytes in P. vivax have been reported [14,2729]. Sliding window plot analysis of Tajima’s D across the full-length pkmsp8 gene also indicated most values below 0 indicating purifying selection (Fig.…”
supporting
confidence: 65%
“…Adhesion and invasion processes are key steps for apicomplexan parasites infection ( 21 ). These processes are mediated by a variety of parasite proteins that interact with host cells ( 22 24 ). Studies have shown that MICs play an important role in the adhesion and invasion of parasites to host cells due to their multiple adhesion domains.…”
Section: Discussionmentioning
confidence: 99%
“…However, the roles of PvRBP1a and of PvRBP2b-TfR1 have not been evaluated specifically in the invasion of Duffy-negative red blood cells. Recently, P. vivax merozoite surface protein-1 paralog (PvMSP1P) and P. vivax glycosylphosphatidylinositol-anchored micronemal antigen (PvGAMA) were shown to bind to both Duffy-positive and Duffy-negative red blood cells, and antibodies against PvMSP1P blocked the related P. knowlesi invasion in Duffy-positive reticulocytes [78][79][80]. Those results suggest that PvGAMA and PvMSP1P are ligands that could be involved in Duffy-independent reticulocyte invasion pathways, although functional demonstration is still lacking.…”
Section: Parasite Side: Pvdbp Duplication And/or Other Parasite Ligands?mentioning
confidence: 94%